Plotting disability in the nineteenth-century novel - Walker Gore, Clare (Edinburgh : Edinburgh University Press, 2020)
This book takes an exciting new approach to characterisation and plot in the Victorian novel, examining the vital narrative work performed by disabled characters.
Intro -- Series Editor's Preface -- Acknowledgements -- Introduction -- Chapter 1 A Possible Person?: Marking the Minor Character in Dickens -- Chapter 2 At the Margins of Mystery: Sensational Difference in Wilkie Collins -- Chapter 3 (De)Forming Families: Disability and the Marriage Plot in Dinah Mulock Craik and Charlotte M. Yonge -- Chapter 4 Terminal Decline: Physical Frailty and Moral Inheritance in George Eliot and Henry James -- Coda -- Bibliography -- Index
Description based on print version record.
JSTOR
Keywords: English fiction -- 19th century -- History and criticism; People with disabilities in literature; Disabilities in literature; Roman anglais -- 19e siècle -- Histoire et critique; Handicap dans la littérature.; Disabilities in literature; English fiction; People with disabilities in literature; Behinderung; Englisch; Roman; Behinderter; Großbritannien; 1800-1899; Criticism, interpretation, etc